Disclosure of Amyloid Status for Risk of Alzheimer Disease to Cognitively Normal Research Participants With Subjective Cognitive Decline: A Longitudinal Study. (12th February 2020) - Wake, Taisei; Tabuchi, Hajime; Funaki, Kei; Ito, Daisuke; Yamagata, Bun; Yoshizaki, Takahito; Nakahara, Tadaki; Jinzaki, Masahiro; Yoshimasu, Haruo; Tanahashi, Iori; Shimazaki, Hiroumi; Mimura, Masaru
This study aimed to investigate the long-term impacts of disclosing amyloid status for a risk of Alzheimer disease (AD) to cognitively normal research participants with subjective cognitive decline (SCD), which represents an initial manifestation of AD. Forty-two participants were classified as the amyloid-positive ( n = 10) or amyloid-negative ( n = 32) groups. We assessed symptoms of anxiety, depression, and test-related distress at 6, 24, and 52 weeks after results disclosure. No difference was found over time in anxiety, depression, and test-related distress in either group. Although no significant differences were observed between groups in anxiety or depression, the amyloid-negative group had a significantly higher level of test-related distress than the amyloid-positive group at 52 weeks. Disclosing amyloid status to cognitively healthy research participants with SCD did not cause significant long-term psychological risks. However, a theoretical spectrum of subjective concern may exist about cognitive decline in amyloid-negative individuals.